-5x-4=x

Simple and best practice solution for -5x-4=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-4=x equation:


Simplifying
-5x + -4 = x

Reorder the terms:
-4 + -5x = x

Solving
-4 + -5x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-4 + -5x + -1x = x + -1x

Combine like terms: -5x + -1x = -6x
-4 + -6x = x + -1x

Combine like terms: x + -1x = 0
-4 + -6x = 0

Add '4' to each side of the equation.
-4 + 4 + -6x = 0 + 4

Combine like terms: -4 + 4 = 0
0 + -6x = 0 + 4
-6x = 0 + 4

Combine like terms: 0 + 4 = 4
-6x = 4

Divide each side by '-6'.
x = -0.6666666667

Simplifying
x = -0.6666666667

See similar equations:

| 7.5x+32.5=94 | | P^2-4p=5 | | 5x-25=-7+2x | | (-7+6i)-(-7-2i)= | | x/y=100000 | | 3z^2-51=0 | | 17+y=34 | | 2(7*3t)=t | | 6m=132 | | 381.2=-9.3x+437 | | 1.6x+.4=12.36+4.2x | | 9p-14=14+3p | | 6.6x-.3=36.24+2.4x | | 9t^2+4t+25-34t=0 | | 4x-15y=-34 | | 5t-4=-7+4t | | 7.5x-.4=-35.66+3.2x | | 3x^2-8/x^3=0 | | log(3)(6x-8)=log(3)(5x+10) | | 5(x+.37)=-41.15 | | 5x+6a=4 | | 9x^2-53x=6 | | 4(2x-1)=8z-4 | | 2y^2+-6y-11=x | | (x+2)(x^2+2x-24)=0 | | 3ln(3u)-4=2 | | 8.7x-.8-4.9x=-38.04 | | 4x^2+-10x+5=0 | | sin(x)=0.2 | | (8t^6)/(-t^6) | | 15s^3-33s^2+29s=11 | | A=(83000.013)9 |

Equations solver categories